Potential of genomics for the improvement of underutilized legumes in sub-Saharan Africa - Paliwal, R.; Adegboyega, T.T.; Abberton, Michael T.; Faloye, B.; Oyatomi, Olaniyi (Wiley, 2021)
Underutilized, or orphan legumes, are widely distributed across farming landscapes in sub-Saharan Africa (SSA) but often have low yields and do not fulfill their potential due to very limited research, breeding, development, marketing, and awareness of their benefits. These advantages include nutritional quality and climate resilience. In this review, we focus on Bambara groundnut, African yam bean, and Kersting's groundnut. Knowledge of the challenges and rewards of exploiting them will provide opportunities for concerted approaches to their revival and contribution to future global food systems, especially in the context of climate change. This review identifies the institutional and noninstitutional challenges, the constraints, the prospects, and the rewards that can be derived from exploiting orphan legumes in SSA. The genetic resources center (GRC) of the International Institute of Tropical Agriculture (IITA) conserves a diverse collection of about 2500 accessions of these crops with the majority from Africa. In this review, we focus on the ex situ conservation of the genetic resources of these indigenous African legume crops, their characterization and evaluation, prospects for the development of improved cultivars, and the role they could play, particularly with respect to nutrition and adaptation to climate change. We emphasize progress made in recent years concerning the assembly of information required for application of genomics tools to these crops and how this will underpin the development of improved varieties.